TRANSFORMASI SEDEKAH SAMPAH MENJADI KURIKULUM FILANTROPI LINGKUNGAN DI MADRASAH IBTIDAIYAH - Ahsan Hakim; Khoiriyah; Benny Prasetiya (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The transformation of an environment-based social program into a madrasah curriculum is an important issue in the development of character education in Islamic elementary schools, particularly when schools are expected to integrate ecological, social, and religious values into students’ learning experiences. This study aims to analyze the transformation of the waste donation program into an environmental philanthropy curriculum, its implementation in madrasah practices, and the supporting and inhibiting factors in its application. This research employed a qualitative approach with a case study design at MI Muhammadiyah 08 Pelangwot, Lamongan. Data were collected through observation, in-depth interviews, focus group discussions, field notes, and document studies involving the principal, vice principal for curriculum affairs, program coordinator, and classroom teachers as the main informants. The data were analyzed through data condensation, data display, and conclusion drawing and verification. The findings show that the waste donation program transformed from a community-based social movement into a madrasah curricular practice through habituation, routine agendas, value reinforcement in learning, and character reflection. The implementation of the environmental philanthropy curriculum is reflected in Friday waste collection activities, school cleaning duties, waste sorting and selling, recording of proceeds, and the interpretation of waste as a medium of charity. The main supporting factors include madrasah leadership, teacher commitment, the role of the program coordinator, and community participation, while the inhibiting factors include students’ consistency, limited facilities, administrative challenges, and character evaluation. This study confirms that waste donation can serve as a contextual curriculum model that integrates character education, environmental education, and Islamic philanthropy in Islamic elementary schools.